Method for preparing PETG biodegradable copolyester from mixed polyester

By combining waste PET polyester with PGA polyester in alcoholylation and polycondensation reactions, PETG biodegradable copolyester is prepared, which solves the problems of complex PET recycling technology and high energy consumption, and achieves efficient and environmentally friendly PET recycling.

CN119613688AActive Publication Date: 2025-03-14TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411714566.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing PET recycling technology has problems such as complex operation, complex process and high energy consumption, making it difficult to effectively utilize waste PET materials.

Method used

PETG biodegradable copolyester is prepared by using waste PET polyester and PGA polyester as raw materials, and polycondensation reaction is carried out under high vacuum conditions. This method uses titanium bimetallic catalysts, which simplifies the process flow and reduces energy consumption.

Benefits of technology

The rapid and effective preparation of PETG biodegradable copolyester is achieved, with simple process, small catalyst usage and low energy consumption. The prepared copolyester is biodegradable and alleviates environmental pollution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156609870000021
    Figure BDA0005156609870000021
  • Figure BDA0005156609870000031
    Figure BDA0005156609870000031
  • Figure BDA0005156609870000032
    Figure BDA0005156609870000032
Patent Text Reader

Abstract

The invention discloses a method for preparing PETG biodegradable copolyester from mixed polyester. The method comprises the following steps: mixing waste PET polyester, PGA polyester, an alcoholysis agent and a catalyst, heating to carry out alcoholysis reaction, controlling alcoholysis reaction conditions to depolymerize PET until the number-average molecular weight is 1000-2000g / mol, stopping the reaction, and then completing condensation polymerization under a high vacuum condition to obtain the PETG copolyester. According to the scheme, the process route is simple, the using amount of the catalyst is small, the catalyst does not need to be supplemented during condensation polymerization, energy consumption is low, conversion from non-degradable PET to biodegradable copolyester is achieved, and the method has important significance for relieving the plastic pollution problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of recycling of waste materials, and more specifically, to a method for preparing PETG biodegradable copolyester by mixing polyester. Background Art

[0002] Polyethylene terephthalate (PET) is a thermoplastic polyester material widely used in packaging, fiber and engineering plastics. It is favored for its excellent mechanical properties, heat resistance and transparency. However, with the increasing production and consumption of PET, serious environmental pollution problems have been caused. The accumulation of waste PET not only occupies land resources, but also puts great pressure on the ecological environment. Therefore, the development of effective PET recycling and reuse technology has become an important topic in today's materials science research.

[0003] At present, the recycling methods of waste PET are mainly divided into physical recycling and chemical recycling. The physical recycling method includes processes such as cleaning, crushing, melting and re-granulation, which can make waste PET into recycled particles, but due to the limitations of raw material purity and impurity content, the performance of its recycled materials is often difficult to meet the needs of high-end applications. Chemical recycling converts waste PET into its raw material monomers through chemical reactions, such as hydrolysis, alcoholysis and pyrolysis. These chemical recycling methods can effectively process complex and mixed PET wastes and generate high-purity raw materials to meet high-standard application requirements. Compared with physical recycling, the advantages of chemical recycling are its higher recovery rate and tolerance to pollutants.

[0004] The patent with publication number CN118374057A discloses a method for preparing PET copolyester by alcoholysis and polymerization of waste PET, but different catalysts need to be used in the alcoholysis and polymerization stages, and stabilizers and antioxidants need to be added to the polymerization system, which is complicated to operate. The patent with publication number CN112441917A discloses a method for recovering terephthalate by transesterification reaction of waste PET and alkyl alcohol, but the product needs to be processed in multiple steps, the process is complicated, and the energy consumption is high. Therefore, a simpler method is needed to recycle PET.

[0005] In recent years, as the concept of sustainable development has gained popularity, research and development based on biodegradable materials has gradually attracted attention. PETG, as a biodegradable copolyester material, has become increasingly popular in the market due to its good processing performance and superior physical properties. Therefore, recycling waste PET to prepare PETG biodegradable copolyester can not only effectively solve the environmental problems of waste PET, but also provide a possible solution for the development of new environmentally friendly materials. Summary of the invention

[0006] Based on the above problems, the first object of the present invention is to provide a method for preparing PETG biodegradable copolyester from mixed polyester. The method uses waste PET polyester and PGA polyester as raw materials, and under the action of an alcoholysis agent and a catalyst, regulates the alcoholysis reaction conditions so that the alcoholysis reaction product can directly undergo a polycondensation reaction to obtain PETG biodegradable copolyester.

[0007] The second object of the present invention is to provide a PETG biodegradable copolyester prepared by the above method.

[0008] In order to achieve the above first object, the present invention adopts the following technical scheme:

[0009] The present invention discloses a method for preparing PETG copolyester by mixing polyester. The method adopts waste PET polyester and PGA polyester as raw materials, belongs to a mixed polyester system, and comprises the following steps:

[0010] Waste PET polyester, PGA polyester, alcoholysis agent and catalyst are mixed, heated for alcoholysis reaction, alcoholysis reaction conditions are controlled to stop the reaction when PET is depolymerized to a number average molecular weight of 1000-2000 g / mol, and then polycondensation reaction is completed under high vacuum conditions to obtain PETG copolyester.

[0011] Furthermore, the alcoholysis agent is selected from ethylene glycol.

[0012] Furthermore, the catalyst is selected from one or more of an antimony catalyst, a germanium catalyst, a rare earth catalyst, and a titanium catalyst, and is preferably a titanium bimetallic catalyst. The preparation method of the titanium bimetallic catalyst is prepared with reference to CN108034046A. The titanium bimetallic catalyst selected in the present invention can catalyze the alcoholysis of PET polyester and PGA polyester, and can also catalyze the synthesis of copolyester, and is a highly efficient catalyst with dual catalytic effects.

[0013] Furthermore, the amount of the alcoholysis agent used is 0.5-10 times the sum of the mass of the waste PET polyester and the PGA polyester.

[0014] Further, the amount of the catalyst is 0.01-0.5% of the sum of the mass of the waste PET polyester and the PGA polyester. Exemplarily, the amount of the catalyst can also be 0.01-0.1%, 0.01-0.2%, 0.01-0.3%, 0.01-0.4%, 0.05-0.1%, 0.05-0.2%, 0.05-0.3%, 0.05-0.4%, 0.05-0.5%, 0.1-0.2%, 0.1-0.3%, 0.1-0.4%, 0.1-0.5%, 0.2-0.3%, 0.2-0.4%, 0.2-0.5%, 0.3-0.4%, 0.3-0.5%, 0.4-0.5%, etc. of the sum of the mass of the waste PET polyester and the PGA polyester.

[0015] Further, the mass ratio of PGA polyester to waste PET polyester is 0.02-0.5. Exemplarily, the mass ratio of PGA polyester to waste PET polyester can also be 0.02-0.1, 0.02-0.2, 0.02-0.3, 0.02-0.4, 0.05-0.1, 0.05-0.2, 0.05-0.3, 0.05-0.4, 0.05-0.5, 0.1-0.2, 0.1-0.3, 0.1-0.4, 0.1-0.5, 0.2-0.3, 0.2-0.4, 0.2-0.5, 0.3-0.4, 0.3-0.5, 0.4-0.5, etc.

[0016] Furthermore, the reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 0.5-8.0 h.

[0017] Furthermore, the reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.

[0018] Furthermore, the vacuum degree in the polycondensation reaction is controlled at 10-100 Pa.

[0019] Furthermore, the waste PET polyester is selected from one or more of waste PET bottles, waste PET films and waste PET fibers, and has a number average molecular weight of 10-40 kg / mol.

[0020] In order to achieve the above second purpose, the present invention adopts the following technical solutions:

[0021] The present invention discloses a PETG biodegradable copolyester prepared by the method as described above, and its structural formula is as follows:

[0022]

[0023] Wherein, x is 1-100, y is 1-3, and the number average molecular weight of the PETG biodegradable copolyester is 10000-50000 g / mol.

[0024] The beneficial effects of the present invention are as follows:

[0025] The invention provides a method for preparing PETG biodegradable copolyester by using waste PET polyester quickly and effectively. Waste PET polyester, PGA polyester, alcoholysis agent and catalyst are mixed to carry out alcoholysis reaction to obtain oligomers, and then polycondensation reaction is completed under certain reaction temperature and high vacuum conditions to obtain PETG copolyester. The scheme has a simple process route, a small amount of catalyst, low energy consumption, and the prepared copolyester has biodegradability, realizing the conversion of non-degradable PET into biodegradable copolyester, which is of great significance for alleviating environmental pollution problems.

[0026] After the alcoholysis reaction is completed, the system does not need any separation step and can skip the esterification stage to directly carry out the polycondensation reaction, which greatly simplifies the process flow and shortens the time cost.

[0027] The catalyst selected in the present invention (such as a titanium-based bimetallic catalyst) can catalyze both alcoholysis of PET polyester and synthesis of copolyester, so that the reaction system can successfully transition from alcoholysis reaction to polycondensation reaction without adding a polycondensation catalyst for a second time in the entire method. At the same time, since the amount of catalyst used in the alcoholysis reaction is relatively small and no new catalyst needs to be added in the subsequent polycondensation reaction, the low metal element content in the recovered polymer is guaranteed.

[0028] The waste PET polyester selected in the present invention has a wide range of sources, and can be waste PET bottles, waste PET films, waste PET fibers, etc. The method realizes the recycling of PET waste into biodegradable copolyester. DETAILED DESCRIPTION

[0029] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0030] The molecular weight and distribution of the polymer were tested by gel permeation chromatography (GPC, e2695, Waters, USA), with chloroform and o-chlorophenol as a mixed solvent, chloroform as the mobile phase, and PMMA as the reference substance.

[0031] The content of metal elements in the polymer was measured using an inductively coupled plasma mass spectrometer (ICP-MS-2030, Shimadzu, Japan) with trifluoroacetic acid as the solvent.

[0032] Using H NMR spectroscopy ( 1 H NMR, Advance 400, Bruker, Germany) was used to determine the structure of the polymer and the content of GA units in the copolyester was calculated.

[0033] The titanium-based bimetallic catalyst used in the following specific examples of the present invention is prepared according to the preparation conditions of Example 1 in CN108034046A.

[0034] Examples 1-8

[0035] The structural formula of PETG copolyester is as follows:

[0036] Wherein, x is 1-10, y is 1-3, and the number average molecular weight of the copolyester is 10000-50000 g / mol.

[0037] Waste PET and PGA are mixed and hydrolyzed and polymerized to prepare PETG copolyester, the steps are as follows:

[0038] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The stirring speed was 300 rpm. After reacting at a certain temperature for a certain time, an oligomer with a number average molecular weight of about 1000-2000 g / mol was obtained.

[0039] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, increase the stirring speed to 450 rpm, and carry out polycondensation at a certain temperature. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0040] In Examples 1-8, the alcoholysis temperature, alcoholysis time, molecular weight of the alcoholysis product, polycondensation temperature and polycondensation time of each example are shown in Table 1, and the molecular weight of the PETG copolyester obtained in each example is shown in Table 2.

[0041] Table 1. Reaction parameters in Examples 1-8

[0042]

[0043]

[0044] Table 2. Molecular weight of PETG copolyesters in Examples 1-8

[0045]

[0046] Examples 9-11

[0047] Waste PET and PGA are mixed and hydrolyzed and polymerized to prepare PETG copolyester, the steps are as follows:

[0048] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and a certain amount of titanium bimetallic catalyst were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The reaction temperature was controlled to be 200°C and the stirring speed was 300 rpm. After a period of reaction, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.

[0049] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0050] In Examples 9-11, the reaction parameters and product conditions are shown in Table 3.

[0051] Table 3. Reaction parameters and product conditions in Examples 9-11

[0052]

[0053] Examples 12-16

[0054] Waste PET and PGA are mixed and hydrolyzed and polymerized to prepare PETG copolyester, the steps are as follows:

[0055] (1) Alcoholysis: Waste PET (100.0 g), a certain amount of PGA, ethylene glycol (300.0 g) and a titanium bimetallic catalyst (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath pot equipped with a mechanical stirrer. The reaction temperature was controlled to be 200°C and the stirring speed was 300 rpm. After a period of reaction, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.

[0056] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0057] In Examples 12-16, the reaction parameters and product conditions are shown in Table 4.

[0058] Table 4. Reaction parameters and product conditions in Examples 12-16

[0059]

[0060] Comparative Example 1

[0061] Waste PET and PGA were mixed and hydrolyzed and polymerized to prepare PETG copolyester, which was different from Example 8 in that the reaction time was extended to hydrolyze the polyester into monomers, and then the polymerization reaction was carried out, and the steps were as follows:

[0062] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled to be 200°C, the stirring speed was 300 rpm, and after 6.0 h of reaction, the yield of the monomer product bis(hydroxyethyl) terephthalate was 75.3%.

[0063] (2) Polymerization: Under normal pressure, the esterification reaction was carried out at 200-240°C for 3.0 hours, and the stirring speed was 450 rpm. Then, the pressure of the reaction system was reduced to below 100 Pa by an oil pump, and the polycondensation reaction was carried out at 250°C. The polycondensation reaction lasted for about 60 minutes. When the viscosity of the polymer increased significantly and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point, and PETG copolyester was obtained.

[0064] Comparative Example 2

[0065] Waste PET and PGA were mixed and hydrolyzed and polymerized to prepare PETG copolyester. The difference from Example 8 is that the reaction time is shortened to hydrolyze the polyester into oligomers with higher molecular weight, and then the polymerization reaction is carried out. The steps are as follows:

[0066] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and titanium bimetallic catalyst (0.16 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 2.5 h, an oligomer with a number average molecular weight of about 5000 g / mol was obtained.

[0067] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 60 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0068] In Example 8 and Comparative Examples 1-2, the reaction parameters and product conditions are shown in Table 5.

[0069] Table 5. Reaction parameters and product conditions in Example 8 and Comparative Examples 1-2

[0070]

[0071] By comparison, it can be found that the alcoholysis and polymerization time will be greatly prolonged when polyester is depolymerized into monomers and then polymerized. When the alcoholysis time is shortened to obtain oligomers with larger molecular weight, the GA unit is difficult to insert into the molecular weight of PET, resulting in a low content of GA units in the copolyester, affecting its biodegradability.

[0072] Comparative Example 3

[0073] Waste PET and PGA were mixed and alcoholyzed and polymerized to prepare PETG copolyester, which was different from Example 8 in that the catalyst used in the reaction was tetrabutyl titanate, and the steps were as follows:

[0074] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.22 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 5.0 h, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.

[0075] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 120 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0076] Comparative Example 4

[0077] Waste PET and PGA were mixed and alcoholyzed and polymerized to prepare PETG copolyester. The difference from Comparative Example 3 was that the amount of tetrabutyl titanate was different. The steps were as follows:

[0078] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.36 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 3.0 h, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.

[0079] (2) Polymerization: Use an oil pump to reduce the pressure of the reaction system to below 100 Pa, raise the temperature of the oil bath to 250°C, and increase the stirring speed to 450 rpm to carry out polycondensation. The polycondensation reaction lasts for about 90 minutes. When the viscosity of the polymer increases significantly and the torque of the stirring device reaches 30 N·cm, the reaction is considered to have reached the end point, and PETG copolyester is obtained.

[0080] Comparative Example 5

[0081] Waste PET and PGA were mixed and alcoholyzed and polymerized to prepare PETG copolyester. The difference from Comparative Example 4 is that tetrabutyl titanate was added twice by alcoholysis and polymerization. The steps are as follows:

[0082] (1) Alcoholysis: Waste PET (100.0 g), PGA (15.0 g), ethylene glycol (300.0 g) and tetrabutyl titanate (0.18 g) were added to a 500 mL three-necked flask, and then the three-necked flask was placed in an oil bath equipped with a mechanical stirrer. The reaction temperature was controlled at 200 °C and the stirring speed was 300 rpm. After reacting for 5.5 h, an oligomer with a number average molecular weight of about 2000 g / mol was obtained.

[0083] (2) Polymerization: Tetrabutyl titanate (0.18 g) was added to the three-necked flask, the pressure of the reaction system was reduced to below 100 Pa using an oil pump, the temperature of the oil bath was raised to 250°C, the stirring speed was increased to 450 rpm, and the polycondensation reaction was carried out. The polycondensation reaction lasted for about 90 minutes. When the viscosity of the polymer increased significantly and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point, and PETG copolyester was obtained.

[0084] In Example 8 and Comparative Examples 3-5, the reaction parameters and product conditions are shown in Table 6.

[0085] Table 6. Reaction parameters and products in Example 8 and Comparative Examples 3-5

[0086]

[0087]

[0088] By comparison, it can be found that when tetrabutyl titanate is used as a catalyst, the reaction efficiency is relatively low compared to titanium-based bimetallic catalysts, and a longer alcoholysis time or more catalysts are required to obtain a copolyester equivalent to that in the example. However, increasing the amount of catalyst may result in a higher content of metal elements in the prepared copolyester.

[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing PETG biodegradable copolyester by mixing polyesters, characterized in that: The steps include: Waste PET polyester, PGA polyester, alcoholysis agent and catalyst are mixed, heated for alcoholysis reaction, alcoholysis reaction conditions are controlled to stop the reaction when PET is depolymerized to a number average molecular weight of 1000-2000g / mol, and then polycondensation reaction is completed under high vacuum conditions to obtain PETG copolyester.

2. The method according to claim 1, characterized in that The alcoholysis agent is selected from ethylene glycol.

3. The method according to claim 1, characterized in that The catalyst is selected from one or more of antimony-based catalysts, germanium-based catalysts, rare earth catalysts, and titanium-based catalysts; preferably, it is a titanium-based bimetallic catalyst.

4. The method according to claim 1, characterized in that: The vacuum degree in the polycondensation reaction is controlled at 10-100 Pa.

5. The method according to claim 1, characterized in that The amount of the alcoholysis agent used is 0.5-10 times the sum of the mass of the waste PET polyester and the PGA polyester.

6. The method according to claim 1, characterized in that The amount of the catalyst used is 0.01-0.5% of the sum of the mass of the waste PET polyester and the PGA polyester.

7. The method according to claim 1, characterized in that The mass ratio of PGA polyester to waste PET polyester is 0.02-0.

5.

8. The method according to claim 1, characterized in that The reaction temperature of the alcoholysis reaction is 180-230° C., and the reaction time of the alcoholysis reaction is 0.5-8.0 h.

9. The method according to claim 1, characterized in that: The reaction temperature of the polycondensation reaction is 240-260° C., and the reaction time of the polycondensation reaction is 0.5-5.0 h.

10. PETG biodegradable copolyester, characterized in that It is prepared by the method according to any one of claims 1 to 9, and its structural formula is as follows: Wherein, x is 1-100, y is 1-3, and the number average molecular weight of the PETG biodegradable copolyester is 10000-50000 g / mol.

Citation Information

Patent Citations

  • Efficient polyester composite catalyst and preparation method and application thereof

    CN108034046A

  • Method for recovering terephthalate from waste PET

    CN112441917A

  • Method for alcoholysis of waste PET and preparation of PET copolyester

    CN118374057A

  • Preparation method of degradable PET-based copolyester

    CN114292388A

  • Method for preparing PETG / PCTG copolyester by depolymerizing waste PET with mixed alcohol

    CN115490839A